Synthesis and utility of new amine/nucleobase addition products of allenylphosphonates - Swamy, K. C. Kumara; Balaraman, Ekambaram; Kumar, N. Satish (Tetrahedron, 2006)
In the reaction of allenylphosphonates with amines/nucleobases, depending on the amine and the allenylphosphonate, either Z- or E-vinylphosphonate or allylphosphonate as a single isomer with a β-amino functionality was isolated. A simple route to phosphonates with a β-NH2 group is developed by direct reaction with ammonia. In reactions with adenine, three different modes of reaction, with one of them involving an unusual cyclisation, are observed. The utility of (enamino)allyl phosphonate products thus obtained in the synthesis of (enamino)-1,3-butadienes via Horner–Wadsworth–Emmons (HWE) reaction is also demonstrated.

Unusual products in the reactions of phosphorus(III) compounds with N=N, C equivalent to C or conjugated double-bonded systems - Swamy, K. C. Kumara; Balaraman, Ekambaram; Pavan, M. Phani; Kumar, N. N. Bhuvan; Kumar, K. Praveen; Kumar, N. Satish (Journal of Chemical Sciences, 2006)
The diversity of products in the reaction of diethyl azodicarboxylate (DEAD)/diisopropyl azodicarboxylate (DIAD) and activated acetylenes with PIII compounds bearing oxygen or nitrogen substituents is discussed. New findings that are useful in understanding the nature of intermediates involved in the Mitsunobu reaction are highlighted. X-ray structures of two new compounds (2-t-Bu-4-MeC6H3O)P (μ-N-t-Bu)2P+[(NH-t-Bu)N[(CO2]-i-Pr)(HNCO2-i-Pr)]](Cl-)(2-t-Bu-4-MeC6H3OH)(23)and [CH2(6-t-Bu-4-Me-C6H2O)2P(O)C(CO2Me)C-(CO2Me)CClNC(O)Cl] (33) are also reported. The structure of23 is close to one of the intermediates proposed in the Mitsunobu reaction.